Honghua extract mediated potent inhibition of COVID-19 host cell pathways - Malika Madikyzy; Meruyert Tilegen; Guldan Nazarbek; Chenglin Mu; Aidana Kutzhanova; Xugang Li; Cuiping Ma; Yingqiu Xie (Scientific Reports, 2022)
Abstract Honghua (Carthami flos) and Xihonghua (Croci stigma) have been used in anti-COVID-19 as Traditional Chinese Medicine, but the mechanism is unclear. In this study, we applied network pharmacology by analysis of active compounds and compound-targets networks, enzyme kinetics assay, signaling pathway analysis and investigated the potential mechanisms of anti-COVID-19. We found that both herbs act on signaling including kinases, response to inflammation and virus. Moreover, crocin likely has an antiviral effect due to its high affinity towards the human ACE2 receptor by simulation. The extract of Honghua and Xihonghua exhibited nanozyme/herbzyme activity of alkaline phosphatase, with distinct fluorescence. Thus, our data suggest the great potential of Honghua in the development of anti-COVID-19 agents.